2020
DOI: 10.1093/jac/dkaa417
|View full text |Cite
|
Sign up to set email alerts
|

Resistance/fitness trade-off is a barrier to the evolution of MarR inactivation mutants in Escherichia coli

Abstract: Background Mutations that inactivate MarR reduce susceptibility to ciprofloxacin and competitive growth fitness in Escherichia coli. Both phenotypes are caused by overexpression of the MarA regulon, which includes the AcrAB-TolC drug efflux pump. Objectives We asked whether compensatory evolution could reduce the fitness cost of MarR-inactivating mutations without affecting resistance to ciprofloxacin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…As has been shown in previous work, marR mutations are energetically costly, and the presence of a marR mutation can decrease fitness without a selective pressure (37). Indeed, marR variants detected clinically in UPEC isolates often include compensatory mutations that mitigate this growth fitness cost but consequently attenuates antimicrobial resistance (37). Likewise, we observed a significant decrease in growth rate of marR mutant strains when compared to the parent WT strain in a quetiapine-free environment.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As has been shown in previous work, marR mutations are energetically costly, and the presence of a marR mutation can decrease fitness without a selective pressure (37). Indeed, marR variants detected clinically in UPEC isolates often include compensatory mutations that mitigate this growth fitness cost but consequently attenuates antimicrobial resistance (37). Likewise, we observed a significant decrease in growth rate of marR mutant strains when compared to the parent WT strain in a quetiapine-free environment.…”
Section: Discussionsupporting
confidence: 82%
“…While we did not observe a significant role for marR mutations in antimicrobial resistance, we demonstrated that these mutations were beneficial for growth in the environment in which quetiapine is present. As has been shown in previous work, marR mutations are energetically costly, and the presence of a marR mutation can decrease fitness without a selective pressure (37). Indeed, marR variants detected clinically in UPEC isolates often include compensatory mutations that mitigate this growth fitness cost but consequently attenuates antimicrobial resistance (37).…”
Section: Discussionmentioning
confidence: 82%
“…Inactivation mutations of MarA have recently been shown to be selected to reduce the fitness cost imposed by mutations in marR , which cause overexpression of marA . 33 Therefore, the selection of marA mutations in this study is most likely due to the presence of a marR S65fs mutation in genetic background rather than the specific cost imposed by the Cip R rpoB mutations. Second-site mutations in RNAP genes ( rpoA, rpoB and rpoC ) were previously shown to reduce the fitness costs imposed by rpoB mutations that increase resistance to rifampicin.…”
Section: Resultsmentioning
confidence: 91%
“…For example, it is reported that the acquisition of mobile bla NDM-5positive plasmids in Enterobacteriaceae or K. pneumoniae showed little fitness cost on host bacteria (Ma et al, 2020;Huang et al, 2021). It is plausible that antibiotic resistance is determined by interactions between the resistance gene and bacterial host, not only by the existence of the resistance gene (Praski Alzrigat et al, 2021). San et al found that a small plasmid pB1000 carrying bla ROB-1 was able to improve bacterial resistance levels by increasing fitness advantages (San Millan and Maclean, 2017;Sun et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%